The role of health insurance in developing the health sector in Iraq - Maryam Muzahem Abbas (Technium Business and Management, 2024)
Ignoring easily accessible information, facts, and expertise is a contributing factor in numerous problems in the healthcare system that lead to poor-quality healthcare services. It makes no sense to manage healthcare systems without the required data since doing so would prohibit the provision of high-quality medical care. An updated description of the Iraqi healthcare system is what this essay seeks to do. On the Iraqi healthcare system, we identified and assessed both published and unpublished data. Within the informational materials, both published and unpublished, are books, journal articles, and official reports and records of the Iraqi Ministry of Health. Also examined was the useful data that can be discovered on websites. The data that were retrieved were all related to healthcare, including information on the organisational structure of the healthcare system, information on national healthcare policies, including the purpose, objective, and beneficial goals, information on the financing of the healthcare system, information on the provision of healthcare services, information on the workforce in the Iraqi healthcare system, information on the health of mothers and kids they have, as well as details on the state of the healthcare system in Iraq.